The Lives of People with Disabilities during the COVID-19 Pandemic (Case Study in Medan Sunggal District, Medan City) - Siregar, Hairani; Nur. R, Siti Hazzah (Budapest International Research and Critics University, 2021)
The purpose of the study was to see how the lives of people with disabilities during the COVID-19 pandemic, including socio-economic life. Do people with disabilities get the same rights as other members of the community. This research was conducted in Medan Sunggal District, Medan City. This study will use qualitative research methods with a descriptive approach. Using data collection techniques from interviews, observations, and documentation studies. The result of this research is that the researcher targets to get scientific publications in the form of the Sinta Journal 3. The results of the study show that all the lives of people with disabilities experience changes during the COVID-19 pandemic like society in general, there is a decrease in income, restrictions on activities, implementation of health protocols and so on. The panic and fear of people with disabilities causes people with disabilities to have a traumatized nature when they meet strangers. However, to get training and empowerment from the government, not all disabilities get this due to the lack of data collection carried out by the local government plus there are families who sometimes still like to hide their children as disabilities so that the government also finds it difficult to collect data which leads to the absence of training and empowerment programs. specifically from the government for persons with disabilities in Medan Sunggal sub-district.